(3eYGgO heOGQS GdGOGQI GdYQHjI hGdJMOjGJ GdeSJbHdjI (B/s ((3GdbGgQI(B: s (3e(B.(3Y(B. (3ddJfejI GdGOGQjI(B, s, 1997)
(3gP GdcJGH YHGQI Yf fOhGJ heDJeQGJ GdefXeI GdYQHjI ddJfejI GdEOGQjI hhKGFb GLJeGY (B<< (3GaGb eSJMOKI hJMOjGJ LOjOI dGOhGQ heeGQSGJ eYGgO heOGQS hcdjGJ GdEOGQI aj GdHdGO GdYQHjI JhfS (B27-28 (3OjSeHQ (B1995s
Keywords: (3GOGQI YGeIs; (3CYeGd GdeDJeQGJs; (3HdGO YQHjIs; (3JMOjGJ eSJbHdjI (B- (3eOGQS GOGQI GdYQHjI eDSSGJ JfejI GOGQjIs; (3eYGgOs